Liquid crystal polyester fiber
Through melting process and high-temperature heat treatment, a liquid crystal fiber with a specific reflux structure was prepared, which solved the problem of high-intensity of the existing liquid crystal dimension and achieved the effect of high tensile strength.
Patent Information
- Application Number
- JP2019566424
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-01-18
- Filing Date
- 2019-01-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2039-01-08
AI Technical Summary
The existing LCD fibers have room for improvement in high strength, and it is difficult to achieve higher tensile strength.
The liquid crystal veins are prepared by melting the veins process to ensure that they contain specific veins, including veins with high 2,6-based content, and to increase the strength of the veins by high temperature heat treatment.
The high strength of the liquid crystal velocity is realized, which is specifically manifested as the tensile strength reaches 25cN/dtex or above, which improves the mechanical properties of the velocity.
Smart Images

Figure 0007658532000003 
Figure 0007658532000001 
Figure 0007658532000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal polyester fiber and a strengthened liquid crystal polyester fiber. This application claims priority based on Japanese Patent Application No. 2018-006322, filed on January 18, 2018, the contents of which are incorporated herein by reference. [Background technology]
[0002] Liquid crystal polyesters have excellent low moisture absorption, heat resistance and thin-wall formability, and are therefore widely used as materials for electronic components, etc. In recent years, studies have been conducted on fiberizing liquid crystal polyesters by taking advantage of these properties of liquid crystal polyesters.
[0003] Liquid crystal polyester fibers made by fiberizing liquid crystal polyester are generally formed by melting the liquid crystal polyester and then stretching it while extruding it through fine holes. In this case, the lower the viscosity of the molten liquid crystal polyester, the finer the fibers can be obtained, and the better the fiberization can be (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-43380 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although fibers formed using conventional liquid crystal polyesters exhibit high strength, there is a demand for even higher strength and there is room for improvement.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a liquid crystal polyester fiber from which a liquid crystal polyester fiber with enhanced strength can be obtained, and a liquid crystal polyester fiber with high strength (for example, tensile strength of 25 cN / dtex or more). [Means for solving the problem]
[0007] In order to solve the above problems, one aspect of the present invention is a fiber obtained by melt spinning a liquid crystalline polyester, the liquid crystalline polyester having repeating units represented by the following formulas (1), (2), and (3), The liquid crystal polyester fiber contains 40 mol % or more of repeating units containing 2,6-naphthylene groups relative to the total content of all repeating units constituting the liquid crystal polyester, and has a degree of orientation in the flow direction of the liquid crystal polyester of 89% or more and 95% or less. (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- (Ar 1 represents a phenylene group, a naphthylene group or a biphenylylene group. 2 and Ar 3 Each of X and Y independently represents an oxygen atom or an imino group (-NH-). 1 , Ar 2 or Ar 3 Each hydrogen atom in the group represented by the following formula may be independently substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.)
[0008] In one embodiment of the present invention, the liquid crystal polyester may contain 65 mol % or more and 85 mol % or less of repeating units containing 2,6-naphthylene groups based on the total content of all repeating units.
[0009] One aspect of the present invention provides a high-strength liquid crystalline polyester fiber obtained by heat treating the above liquid crystalline polyester fiber at a temperature of 250° C. or higher.
[0010] That is, the present invention includes the following aspects. [1] A fiber containing liquid crystal polyester, The liquid crystal polyester has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3), at least one repeating unit selected from the group consisting of a repeating unit represented by formula (1), a repeating unit represented by formula (2), and a repeating unit represented by formula (3) contains a 2,6-naphthylene group; the content of the repeating unit containing the 2,6-naphthylene group is 40 mol % or more based on the total content of all repeating units constituting the liquid crystal polyester, The orientation degree of the liquid crystal polyester in the length direction of the fibers is 89% or more and 95% or less. Liquid crystal polyester fiber. (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- (Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, or a biphenylylene group, and Ar 1 , Ar 2 and Ar 3 At least one selected from the group consisting of contains a 2,6-naphthylene group. X and Y each independently represent an oxygen atom or an imino group (-NH-). Ar 1 , Ar 2 or Ar 3 Each hydrogen atom in the group represented by the formula (I) may be independently substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms. [2] The liquid crystal polyester fiber according to [1], wherein the content of the repeating unit containing the 2,6-naphthylene group is 65 mol % or more and 85 mol % or less based on the total content of all repeating units constituting the liquid crystal polyester. [3] A fiber containing liquid crystal polyester, A liquid crystal polyester fiber having a tensile strength of 25 cN / dtex or more and 30 cN / dtex or less. [4] The liquid crystalline polyester fiber according to [3], wherein the orientation degree of the liquid crystalline polyester in the length direction of the fiber is 94% or more and less than 100%. [5] The liquid crystalline polyester has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3): at least one repeating unit selected from the group consisting of a repeating unit represented by formula (1), a repeating unit represented by formula (2), and a repeating unit represented by formula (3) contains a 2,6-naphthylene group; The liquid crystal polyester fiber according to [3] or [4], wherein the content of the repeating unit containing the 2,6-naphthylene group is 40 mol % or more based on the total content of all repeating units constituting the liquid crystal polyester. (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- (Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, or a biphenylylene group, and Ar 1 , Ar 2 and Ar 3 At least one selected from the group consisting of contains a 2,6-naphthylene group. X and Y each independently represent an oxygen atom or an imino group (-NH-). Ar 1 , Ar 2 or Ar 3Each hydrogen atom in the group represented by the formula (I) may be independently substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms. [6] The liquid crystal polyester fiber according to [5], wherein the content of the repeating unit containing the 2,6-naphthylene group is 65 mol % or more and 85 mol % or less based on the total content of all repeating units constituting the liquid crystal polyester. Effect of the Invention
[0011] According to one aspect of the present invention, there are provided a liquid crystal polyester fiber which can provide a liquid crystal polyester fiber having enhanced strength, and a liquid crystal polyester fiber having enhanced strength. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of a spinning apparatus for the production method of the liquid crystal polyester fiber of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The liquid crystal polyester fiber and the strengthened liquid crystal polyester fiber of the present embodiment will be described.
[0014] The liquid crystal polyester fiber of the present embodiment is obtained by melt spinning the liquid crystal polyester using the method described below. In this specification, the material obtained by molding the liquid crystal polyester into pellets is also called "liquid crystal polyester".
[0015] [Liquid crystal polyester] The liquid crystal polyester of the liquid crystal polyester fiber of the present embodiment preferably exhibits liquid crystallinity in a molten state and melts at a temperature of 300° C. or more and 450° C. or less. The liquid crystal polyester may be a liquid crystal polyester amide, a liquid crystal polyester ether, a liquid crystal polyester carbonate, or a liquid crystal polyester imide. The liquid crystal polyester is preferably a wholly aromatic liquid crystal polyester obtained by using only aromatic compounds as raw material monomers.
[0016] Typical examples of liquid crystal polyesters are: (I) A polymer obtained by polymerizing (polycondensing) an aromatic hydroxycarboxylic acid, an aromatic dicarboxylic acid, and at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine; (II) a polymer obtained by polymerizing a plurality of aromatic hydroxycarboxylic acids; (III) a polymer obtained by polymerizing an aromatic dicarboxylic acid with at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxylamine, and an aromatic diamine; and (IV) Polymers obtained by polymerizing a polyester such as polyethylene terephthalate with an aromatic hydroxycarboxylic acid. The aromatic hydroxycarboxylic acid, the aromatic dicarboxylic acid, the aromatic diol, the aromatic hydroxyamine or the aromatic diamine contains a 2,6-naphthylene group.
[0017] Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine may each independently be replaced in whole or in part by a polymerizable derivative thereof.
[0018] Examples of polymerizable derivatives of compounds having a carboxyl group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include those in which the carboxyl group has been converted into an alkoxycarbonyl group or an aryloxycarbonyl group (i.e., esters), those in which the carboxyl group has been converted into a haloformyl group (i.e., acid halides), and those in which the carboxyl group has been converted into an acyloxycarbonyl group (i.e., acid anhydrides).
[0019] Examples of polymerizable derivatives of compounds having a hydroxy group, such as aromatic hydroxycarboxylic acids, aromatic diols and aromatic hydroxyamines, include those obtained by converting the hydroxy group into an acyloxyl group through acylation (i.e., acylated products).
[0020] Examples of polymerizable derivatives of compounds having an amino group, such as aromatic hydroxyamines and aromatic diamines, include those obtained by acylation of the amino group to convert it into an acylamino group (acylated products of amino groups).
[0021] The liquid crystal polyester fiber of this embodiment has a repeating unit represented by the following formula (1) (hereinafter, sometimes referred to as "repeating unit (1)"), a repeating unit represented by the following formula (2) (hereinafter, sometimes referred to as "repeating unit (2)"), and a repeating unit represented by the following formula (3) (hereinafter, sometimes referred to as "repeating unit (3)"). (1)-O-Ar 1 -CO- (2)-CO-Ar 2 -CO- (3)-X-Ar 3 -Y- (Ar 1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar 2 and Ar 3 each independently represents a phenylene group, a naphthylene group, or a biphenylylene group, and Ar 1 , Ar 2 and Ar 3At least one selected from the group consisting of contains a 2,6-naphthylene group. X and Y each independently represent an oxygen atom or an imino group (-NH-). Ar 1 , Ar 2 or Ar 3 Each hydrogen atom in the group represented by the formula (I) may be independently substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0022] The halogen atom includes a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0023] The alkyl group is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group, an n-octyl group, and an n-decyl group.
[0024] The aryl group is preferably an aryl group having 6 to 20 carbon atoms, and examples thereof include a phenyl group, an o-tolyl group, a m-tolyl group, a p-tolyl group, a 1-naphthyl group, and a 2-naphthyl group.
[0025] Ar 1 , Ar 2 or Ar 3 When hydrogen atoms in the group represented by the formula: 1 , Ar 2 or Ar 3 For each of the groups represented by the following formula (I), the number is, for example, 2 or less, and preferably 1.
[0026] The repeating unit (1) is a repeating unit derived from a specific aromatic hydroxycarboxylic acid.
[0027] In this specification, the term "derived from" means that the chemical structure is changed due to the polymerization of the raw material monomer, and no other structural changes occur.
[0028] The repeating unit (1) is Ar 1 is a p-phenylene group (e.g., a repeat unit derived from p-hydroxybenzoic acid), and Ar 1 is a 2,6-naphthylene group (for example, a repeating unit derived from 6-hydroxy-2-naphthoic acid).
[0029] The repeating unit (2) is a repeating unit derived from a specific aromatic dicarboxylic acid. 2 is a p-phenylene group (e.g., a repeating unit derived from terephthalic acid), Ar 2 is an m-phenylene group (e.g., a repeating unit derived from isophthalic acid), Ar 2 is a 2,6-naphthylene group (e.g., a repeat unit derived from 2,6-naphthalenedicarboxylic acid), and Ar 2 is a diphenylether-4,4'-diyl group (for example, a repeating unit derived from diphenylether-4,4'-dicarboxylic acid).
[0030] The repeating unit (3) is a repeating unit derived from a specific aromatic diol, aromatic hydroxylamine, or aromatic diamine. The repeating unit (3) is, for example, Ar 3 is a p-phenylene group (e.g., repeat units derived from hydroquinone, p-aminophenol, or p-phenylenediamine), and Ar 3 is a 4,4'-biphenylylene group (for example, a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0031] The content of the repeating unit (1) is, for example, 30 mol % or more, preferably 30% to 80 mol %, more preferably 40% to 70 mol %, and even more preferably 45% to 65 mol %, relative to the total amount of all repeating units constituting the liquid crystal polyester (i.e., the mass of each repeating unit constituting the liquid crystal polyester is divided by the formula weight of each repeating unit to determine the substance amount equivalent (mol) of each repeating unit, and the total value).
[0032] The content of the repeating unit (2) is, for example, 35 mol % or less, preferably 10% or more and 35 mol % or less, more preferably 15% or more and 30 mol % or less, and even more preferably 17.5% or more and 27.5 mol % or less, based on the total amount of all repeating units constituting the liquid crystal polyester.
[0033] The content of the repeating unit (3) is, for example, 35 mol % or less, preferably 10% or more and 35 mol % or less, more preferably 15% or more and 30 mol % or less, and even more preferably 17.5% or more and 27.5 mol % or less, based on the total amount of all repeating units constituting the liquid crystal polyester.
[0034] Liquid crystal polyesters having such a specific repeating unit composition have an excellent balance between heat resistance and moldability. The higher the content of the repeating unit (1), the easier it is to improve the melt flowability and the heat resistance, strength, and rigidity of the molded product. However, if the content is too high, the melting temperature and melt viscosity tend to be high, and the temperature required for molding tends to be high. As one aspect, when the content of the repeating unit (1) is within the above range, the melt fluidity and the heat resistance, strength, and rigidity of the molded article are likely to be improved, and the melt temperature and melt viscosity are likely to be adjusted to be suitable for molding.
[0035] It is preferable that the content of the repeating unit (2) is substantially equal to the content of the repeating unit (3). That is, the ratio of the content of the repeating unit (2) to the content of the repeating unit (3), expressed as [content of the repeating unit (2)] / [content of the repeating unit (3)] (mol / mol), is, for example, 0.9 / 1 to 1 / 0.9, preferably 0.95 / 1 to 1 / 0.95, and more preferably 0.98 / 1 to 1 / 0.98.
[0036] The liquid crystal polyester may have two or more kinds of repeating units (1) to (3) independently. The liquid crystal polyester may have repeating units other than the repeating units (1) to (3), but the content thereof is, for example, 10 mol % or less, and preferably 5 mol % or less, based on the total amount of all repeating units constituting the liquid crystal polyester. In one aspect, the total content of the repeating units (1), (2), and (3) is from 90 mol % to 100 mol %, and preferably from 95 mol % to 100 mol %, based on the total amount of all repeating units constituting the liquid crystal polyester.
[0037] The liquid crystal polyester of the liquid crystal polyester fiber of this embodiment preferably has a repeating unit (3) in which X and Y are each an oxygen atom. That is, the liquid crystal polyester preferably has a repeating unit derived from a specific aromatic diol. This makes it easy to lower the melt viscosity of the liquid crystal polyester. It is more preferable that the liquid crystal polyester only has a repeating unit (3) in which X and Y are each an oxygen atom.
[0038] The liquid crystal polyester fiber of the present embodiment has a repeating unit content containing 2,6-naphthylene group of 40 mol% or more with respect to the total content of all repeating units constituting the liquid crystal polyester. When the liquid crystal polyester fiber made of such liquid crystal polyester is subjected to a heat treatment process described later, a liquid crystal polyester fiber having enhanced strength is obtained. In addition, a liquid crystal polyester fiber having excellent electrical properties (e.g., low dielectric tangent) is obtained. In addition, it is preferable that the repeating unit content containing 2,6-naphthylene group is 85 mol% or less with respect to the total content of all repeating units constituting the liquid crystal polyester. Furthermore, the liquid crystal polyester according to the present embodiment of the liquid crystal polyester fiber has a repeating unit (1) Ar 1 is a 1,4-phenylene group, and Ar 2 is either a 1,4-phenylene group or a 1,3-phenylene group, and Ar 3 When the copolymer contains a 4,4'-biphenylylene group, the strength and elastic modulus of the resulting fiber are excellent.
[0039] In the liquid crystal polyester fiber of this embodiment, the content of repeating units containing 2,6-naphthylene groups is preferably 65 mol% or more, more preferably 68 mol% or more, and even more preferably 70 mol% or more, based on the total content of all repeating units constituting the liquid crystal polyester.
[0040] In the liquid crystal polyester, the content of repeating units containing a 2,6-naphthylene group is preferably 82 mol % or less, and more preferably 80 mol % or less, based on the total content of all repeating units constituting the liquid crystal polyester.
[0041] The above upper and lower limits can be combined in any desired manner. In one aspect, the content of the repeating unit containing the 2,6-naphthylene group is 40 mol% or more and 85 mol% or less, preferably 65 mol% or more and 85 mol% or less, more preferably 65 mol% or more and 82 mol% or less, even more preferably 68 mol% or more and 80 mol% or less, particularly preferably 70 mol% or more and 80 mol% or less, and extremely preferably 72 mol% or more and 77 mol% or less, based on the total content of all repeating units constituting the liquid crystal polyester.
[0042] In another aspect, the liquid crystal polyester according to the liquid crystal polyester fiber of the present embodiment has a repeating unit (1), a repeating unit (2), and a repeating unit (3), at least one repeating unit selected from the group consisting of a repeating unit represented by formula (1), a repeating unit represented by formula (2), and a repeating unit represented by formula (3) contains a 2,6-naphthylene group; Relative to the total amount of all repeating units constituting the liquid crystal polyester, The content of the repeating unit (1) is 30 mol % or more, preferably 30 mol % or more and 80 mol % or less, more preferably 40 mol % or more and 70 mol % or less, and further preferably 45 mol % or more and 65 mol % or less, the content of the repeating unit (2) is 35 mol% or less, preferably from 10% to 35 mol%, more preferably from 15% to 30 mol%, and even more preferably from 17.5% to 27.5 mol%, the content of the repeating unit (3) is 35 mol% or less, preferably from 10% to 35 mol%, more preferably from 15% to 30 mol%, and even more preferably from 17.5% to 27.5 mol%, However, the total content of the repeating unit (1), the repeating unit (2) and the repeating unit (3) does not exceed 100 mol %, The content of the repeating unit containing the 2,6-naphthylene group is 40 mol% or more and 85 mol% or less, preferably 65 mol% or more and 85 mol% or less, more preferably 65 mol% or more and 82 mol% or less, even more preferably 68 mol% or more and 80 mol% or less, particularly preferably 70 mol% or more and 80 mol% or less, and extremely preferably 72 mol% or more and 77 mol% or less, relative to the total content of all repeating units constituting the liquid crystal polyester.
[0043] The repeating unit (1) is Ar 1 is a 2,6-naphthylene group (for example, a repeating unit derived from 6-hydroxy-2-naphthoic acid).
[0044] The repeating unit (2) is Ar 2 is a 2,6-naphthylene group (e.g., a repeat unit derived from 2,6-naphthalenedicarboxylic acid), and Ar 2 is a 1,4-phenylene group (a repeating unit derived from terephthalic acid).
[0045] The repeating unit (3) is Ar 3 is a 1,4-phenylene group (e.g., a repeat unit derived from hydroquinone), and Ar 3 is a 4,4'-biphenylylene group (for example, a repeating unit derived from 4,4'-dihydroxybiphenyl).
[0046] Liquid crystal polyesters having high heat resistance and melt tension are those which (i) contain Ar 1 The repeating unit (1) is a 2,6-naphthylene group, i.e., the repeating unit derived from 6-hydroxy-2-naphthoic acid is preferably 40 mol % or more and 70 mol % or less, more preferably 45 mol % or more and 65 mol % or less, and even more preferably 50 mol % or more and 60 mol % or less, (ii) Ar 2The repeating unit (2) in which m is a 2,6-naphthylene group, i.e., the repeating unit derived from 2,6-naphthalenedicarboxylic acid, is preferably present in an amount of from 10 mol % to 30 mol %, more preferably from 12.5 mol % to 27.5 mol %, and even more preferably from 15 mol % to 25 mol %, (iii) Ar 2 the repeating unit (2) having a 1,4-phenylene group, i.e., a repeating unit derived from terephthalic acid, is preferably from 0 mol % to 15 mol %, more preferably from 0 mol % to 12 mol %, and even more preferably from 0 mol % to 10 mol %, (iv) Ar 3 The repeating unit (3) is a 1,4-phenylene group, i.e., a repeating unit derived from hydroquinone, or the repeating unit (3) is a 4,4'-biphenylylene group, i.e., a repeating unit derived from 4,4'-dihydroxybiphenyl, in an amount of preferably 12.5 mol % to 30 mol %, more preferably 17.5 mol % to 30 mol %, and even more preferably 20 mol % to 25 mol %, and (v) Ar 2 and Ar 3 are substantially equimolar (i.e., (the total content of repeating units derived from 2,6-naphthalenedicarboxylic acid and repeating units derived from terephthalic acid) / (the content of repeating units derived from hydroquinone or repeating units derived from 4,4'-dihydroxybiphenyl) (mol / mol) is 0.9 / 1 to 1 / 0.9, preferably 0.95 / 1 to 1 / 0.95, and more preferably 0.98 / 1 to 1 / 0.98). Also, the highly sublimable component may be contained in an excess amount within a range of less than 1 mol %.
[0047] As one aspect, the liquid crystal polyester according to the liquid crystal polyester fiber of the present embodiment is Relative to the total amount of all repeating units constituting the liquid crystal polyester, the content of repeating units derived from 6-hydroxy-2-naphthoic acid is 40 mol% or more and 70 mol% or less, preferably 45 mol% or more and 65 mol% or less, and more preferably 50 mol% or more and 60 mol% or less; the content of repeating units derived from 2,6-naphthalenedicarboxylic acid is 10 mol % or more and 30 mol % or less, preferably 12.5 mol % or more and 27.5 mol % or less, and more preferably 15 mol % or more and 25 mol % or less; the content of repeating units derived from terephthalic acid is 0 mol% or more and 15 mol% or less, preferably 0 mol% or more and 12 mol% or less, and more preferably 0 mol% or more and 10 mol% or less; The content of repeating units derived from hydroquinone or repeating units derived from 4,4'-dihydroxybiphenyl is 12.5 mol% or more and 30 mol% or less, preferably 17.5 mol% or more and 30 mol% or less, more preferably 20 mol% or more and 25 mol% or less, and (the total content of the repeating units derived from 2,6-naphthalenedicarboxylic acid and the repeating units derived from terephthalic acid) / (the content of the repeating units derived from hydroquinone or the repeating units derived from 4,4'-dihydroxybiphenyl) (mol / mol) is 0.9 / 1 to 1 / 0.9, preferably 0.95 / 1 to 1 / 0.95, and more preferably 0.98 / 1 to 1 / 0.98. It is a liquid crystal polyester.
[0048] The liquid crystal polyester relating to the liquid crystal polyester fiber of this embodiment can be produced by polymerizing (polycondensing) the monomers having a 2,6-naphthylene group in a total amount (the total amount of 6-hydroxy-2-naphthoic acid, 2,6-naphthalenedicarboxylic acid, and 2,6-naphthalenediol) in an amount of 40 mol % or more and 85 mol % or less based on the total amount of all monomers.
[0049] The liquid crystal polyester according to the liquid crystal polyester fiber of the present embodiment is preferably produced by melt-polymerizing raw material monomers corresponding to the repeating units constituting the liquid crystal polyester fiber, and solid-phase polymerizing the resulting polymer (hereinafter, sometimes referred to as "prepolymer"). This allows a high molecular weight liquid crystal polyester having high heat resistance, strength, and rigidity to be produced with good operability. The melt polymerization may be carried out in the presence of a catalyst, and examples of the catalyst include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, and antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole, and nitrogen-containing heterocyclic compounds are preferably used.
[0050] The liquid crystal polyester used as a raw material for the liquid crystal polyester fiber has a flow initiation temperature of, for example, 280° C. or higher, preferably 280° C. or higher and 400° C. or lower, and more preferably 280° C. or higher and 360° C. or lower. The higher the flow initiation temperature, the easier it is to improve heat resistance, strength, and rigidity, but if it is too high, the melting temperature and melt viscosity are likely to be high, and fiberization tends to be difficult. That is, when the flow starting temperature is within the above range, the heat resistance, strength and rigidity are easily improved, and the melting temperature and melt viscosity are easily adjusted to be suitable for fiberization.
[0051] The flow initiation temperature is also called the flow temperature or fluidity temperature, and is the temperature at which the liquid crystalline polyester shows a viscosity of 4800 Pa s (48000 poise) when it is melted and extruded from a nozzle with an inner diameter of 1 mm and a length of 10 mm using a capillary rheometer while heating at a rate of 4°C / min under a load of 9.8 MPa (100 kg / cm2), and is an indicator of the molecular weight of the liquid crystalline polyester (see "Liquid Crystal Polymer - Synthesis, Molding, Applications" edited by Koide Naoyuki, CMC Corporation, June 5, 1987, p. 95).
[0052] The liquid crystal polyester relating to the liquid crystal polyester fiber of the present embodiment is preferably melt-kneaded using an extruder and then molded into pellets.
[0053] The extruder preferably has a cylinder, at least one screw disposed in the cylinder, and at least one supply port provided in the cylinder. Furthermore, the extruder more preferably has at least one vent provided in the cylinder. In addition, it is preferable to use an extruder equipped with a kneading section downstream of the supply port (in the case where a plurality of supply ports are provided, downstream of each supply port). Here, the kneading section refers to a part provided in a part of the screw for efficiently performing melt kneading. Examples of the kneading section include a kneading disc (right kneading disc, neutral kneading disc, right kneading disc), a mixing screw, and the like.
[0054] The extruder is preferably connected to a pressure reducing device at a location having at least one vent. By degassing the inside of the cylinder of the extruder using the pressure reducing device during melt-kneading of the liquid crystal polyester, it is possible to remove low molecular weight components remaining from the liquid crystal polyester.
[0055] [Liquid crystal polyester fiber and highly strengthened liquid crystal polyester fiber] The liquid crystal polyester fiber of the present embodiment can be obtained by melt spinning the liquid crystal polyester described above. As one aspect, the liquid crystal polyester fiber of the present embodiment preferably has a fiber diameter of 5 to 100 μm.
[0056] Moreover, by further heat-treating the liquid crystal polyester fiber of the present embodiment at a temperature of 250° C. or more and 350° C. or less, a liquid crystal polyester fiber having higher strength than the liquid crystal polyester fiber before the heat treatment can be obtained.
[0057] This is believed to be because the liquid crystal polyester in the liquid crystal polyester fiber is made to have a high molecular weight by heat-treating the liquid crystal polyester fiber at a temperature of 250° C. or higher. This can be inferred from the fact that the liquid crystal polyester fiber becomes insoluble or poorly soluble in a good solvent for the liquid crystal polyester fiber.
[0058] The orientation degree of the liquid crystal polyester in the flow direction (MD direction) of the liquid crystal polyester fiber of this embodiment is 89% or more and 95% or less. The higher the orientation degree of the liquid crystal polyester in the MD direction of the liquid crystal polyester fiber, the easier it is to align the orientation direction of the liquid crystal polyester in the liquid crystal polyester fiber. This is considered to increase the strength of the liquid crystal polyester fiber in the MD direction. Therefore, it is considered that the strength of the liquid crystal polyester fiber finally obtained is also increased. In this specification, the "flow direction of the liquid crystal polyester in the liquid crystal polyester fiber" or "MD direction" means the length direction of the liquid crystal polyester fiber, and the "flow direction" and "MD direction" may be referred to as the "length direction of the fiber", and the "degree of orientation in the flow direction" may be referred to as the "degree of orientation in the length direction of the fiber".
[0059] For these reasons, the orientation degree of the liquid crystal polyester in the length direction of the liquid crystal polyester fibers is preferably 90% or more, more preferably 93% or more, and even more preferably 94% or more.
[0060] However, the inventors' investigations have revealed that if the orientation degree of the liquid crystal polyester in the length direction of the liquid crystal polyester fiber is too high (for example, exceeds 95%), the strength of the liquid crystal polyester fiber does not improve even if it is subjected to heat treatment, and a liquid crystal polyester fiber with high strength cannot be obtained. It has been found that such a phenomenon occurs regardless of the structure of the liquid crystal polyester, so long as the liquid crystal polyester contains 40 mol % or more of repeating units containing 2,6-naphthylene groups relative to the total content of all repeating units constituting the liquid crystal polyester.
[0061] The inventors predicted that if the orientation degree in the length direction of the liquid crystal polyester fiber is too high (more than 95%), the liquid crystal polyester has a structure that makes it difficult to increase the molecular weight. Therefore, the inventors attempted to increase the molecular weight of the liquid crystal polyester in the liquid crystal polyester fiber by increasing the heat treatment time of the liquid crystal polyester fiber, thereby improving the strength of the liquid crystal polyester fiber.
[0062] However, it was found that the strength of the liquid crystal polyester fiber does not improve even if the heat treatment time of the liquid crystal polyester fiber is extended. From the above, although the cause is unclear, it can be said that if the orientation degree of the liquid crystal polyester fiber in the length direction of the liquid crystal polyester fiber is too high (more than 95%), the increase in the strength of the liquid crystal polyester fiber before and after the heat treatment process is small, and a liquid crystal polyester fiber with high strength cannot be obtained. Therefore, it is preferable that the orientation degree of the liquid crystal polyester fiber in the length direction of the liquid crystal polyester fiber in the liquid crystal polyester fiber of this embodiment is 95% or less.
[0063] In the liquid crystal polyester fiber of this embodiment, the upper limit value and the lower limit value of the orientation degree in the length direction of the liquid crystal polyester fiber can be combined arbitrarily. In one aspect, the orientation degree of the liquid crystal polyester fiber in the length direction is preferably 90% or more and 95% or less, more preferably 93% or more and 95% or less, and particularly preferably 94% or more and 95% or less.
[0064] The orientation degree of the liquid crystal polyester in the length direction of the liquid crystal polyester fiber of this embodiment is adjusted to a range of 89% or more and 95% or less by appropriately controlling the conditions of the fiberization step and the winding step described later.
[0065] The liquid crystal polyester fiber of the present embodiment may contain resins or additives other than liquid crystal polyester. However, in order to increase the strength of the liquid crystal polyester, the content of the liquid crystal polyester is preferably 80 mass % or more and 100 mass % or less with respect to the total mass of the liquid crystal polyester fiber.
[0066] (Orientation degree) The orientation degree of the liquid crystal polyester fiber in the length direction in the liquid crystal polyester fiber and the strengthened liquid crystal polyester fiber is calculated based on the following formula (S1). The half-width W can be determined by using a rotating anticathode type X-ray diffractometer RINT2500 manufactured by Rigaku Corporation, fixing the diffraction angle 2θ to a diffraction peak around 20°, and measuring the intensity distribution of the diffraction peak of the Debye ring from 0° to 360°. W in formula (S1) represents the half-width (unit: °) of the diffraction peak intensity. Fiber length orientation (%) = {(360-ΣW) / 360}×100 (S1)
[0067] [Liquid crystal polyester fiber and its manufacturing method] The method for producing a liquid crystal polyester fiber of the present embodiment will be described with reference to the drawings. Fig. 1 is a schematic diagram showing an example of a spinning device used in the method for producing a liquid crystal polyester fiber of the present embodiment.
[0068] The spinning device 1 includes an extruder 11 , a gear pump 12 , a nozzle unit 13 , a take-up roller 14 , a winding unit 15 , and a resin flow path 16 .
[0069] In addition, the spinning device 1 may be equipped with a filter made of stainless steel or the like provided in the middle of the resin flow path 16, and an application device for applying a binder, oil, etc. provided between the nozzle portion 13 and the take-up roller 14.
[0070] The extruder 11 and the nozzle portion 13 are connected by a resin flow path 16. The gear pump 12 is provided midway through the resin flow path 16. The take-up roller 14 is provided below the nozzle portion 13.
[0071] The method for producing the liquid crystal polyester fiber (melt spinning) of the present embodiment includes a melting step, a fiber forming step, and a winding step.
[0072] (Melting process) In the melting step according to this embodiment, the liquid crystal polyester is melted by the extruder 11 at a temperature equal to or higher than the flow initiation temperature.
[0073] The extruder 11 is not particularly limited as long as it can melt the liquid crystal polyester at a temperature equal to or higher than the flow initiation temperature, and may be a single screw extruder or a twin screw extruder.
[0074] The melting temperature and melting time of the liquid crystal polyester in the extruder 11 are preferably adjusted within a range in which the liquid crystal polyester does not decompose during melting. For example, the melting temperature is preferably 330 to 370° C., and the melting time is preferably 5 to 30 minutes.
[0075] In addition, the liquid crystal polyester used for the liquid crystal polyester fiber may also contain light stabilizers, various particles such as carbon black and titanium oxide, colorants such as pigments and dyes, antistatic agents, antioxidants, etc., within the range not impairing the effects of the present invention.
[0076] (Fiberization process) In the fiberization step according to this embodiment, the molten liquid crystal polyester is pumped to the nozzle portion 13 by the gear pump 12 and extruded from the nozzle portion 13 to obtain a single fiber of the liquid crystal polyester.
[0077] The nozzle section 13 has a plurality of nozzles. The nozzle hole diameter is preferably 0.05 mm or more and 0.20 mm or less, and more preferably 0.07 mm or more and 0.15 mm or less. If the nozzle hole diameter is 0.20 mm or less, strong shear stress is likely to be applied to the liquid crystal polyester extruded from the nozzle. As a result, the orientation degree of the liquid crystal polyester fiber in the length direction of the liquid crystal polyester in the liquid crystal polyester fiber is likely to be high. On the other hand, if the nozzle hole diameter is 0.05 mm or more, there is little risk of the liquid crystal polyester clogging the nozzle.
[0078] The amount of liquid crystal polyester discharged from the nozzle portion 13 is preferably adjusted within a range in which the liquid crystal polyester fiber does not break during melt spinning. The amount of liquid crystal polyester discharged is, for example, 1 to 40 g / min, and preferably 10 to 30 g / min.
[0079] The shear rate in the nozzle portion 13 is 10000 s -1 More than 100000s -1 It is preferable that the value is less than 30,000s -1 More than 80000s -1 It is more preferable that the shear rate is 10000 s or less. -1 If the shear rate is 100,000 s or more, a strong shear stress is likely to be applied to the liquid crystal polyester extruded from the nozzle. As a result, the orientation degree of the liquid crystal polyester fiber in the length direction of the liquid crystal polyester is likely to be high. -1 If it is equal to or less than this, there is little risk of the liquid crystal polyester fiber breaking during melt spinning.
[0080] The number of nozzle holes in the nozzle portion 13 is not particularly limited, and may be appropriately selected depending on the type of melt spinning device used and the required production volume.
[0081] (winding process) The winding step in the manufacturing method of the liquid crystal polyester fiber of the present embodiment includes obtaining a liquid crystal polyester fiber composed of a plurality of single fibers by taking up a plurality of single fibers with a take-up roller 14 and winding the single fibers on a bobbin made of SUS or the like with a winding unit 15. The liquid crystal polyester fiber in this case is a fiber called a multifilament.
[0082] The winding speed of the liquid crystal polyester fiber in the winding section 15 is preferably 200 m / min or more and 1500 m / min or less, and more preferably 400 m / min or more and 1200 m / min or less. When the winding speed of the liquid crystal polyester fiber is 200 m / min or more, the liquid crystal polyester in the liquid crystal polyester fiber is easily stretched in the longitudinal direction. As a result, the orientation degree of the liquid crystal polyester fiber in the longitudinal direction of the liquid crystal polyester in the liquid crystal polyester fiber is easily increased. On the other hand, when the winding speed of the liquid crystal polyester fiber is 1500 m / min or less, there is little risk of the liquid crystal polyester fiber breaking.
[0083] The liquid crystal polyester fiber obtained after the winding process of this embodiment is called "as-spun fiber". The strength of the liquid crystal polyester fiber of this embodiment is about 5 to 8 cN / dtex. It can be said that the strength of the liquid crystal polyester fiber of this embodiment is higher than the strength of organic fibers made of nylon or polyester other than liquid crystal polyester.
[0084] The strength of the liquid crystal polyester fiber refers to the tensile strength measured using a tensile tester, for example, Autograph AG-1KNIS manufactured by Shimadzu Corporation, at a measurement temperature of 23° C., a sample interval of 20 cm, and a pulling speed of 20 cm / min.
[0085] The orientation degree of the liquid crystal polyester fibers in the longitudinal direction of the liquid crystal polyester fiber in this embodiment is adjusted to a range of 89% or more and 95% or less based on the relationship between the orientation degree of the liquid crystal polyester fibers in the longitudinal direction of the liquid crystal polyester fiber, the shear speed in the nozzle portion 13, and the winding speed in the winding portion 15.
[0086] [High-strength liquid crystal polyester fiber] The liquid crystal polyester fiber of the present embodiment may be further subjected to a heat treatment, if necessary. By subjecting the liquid crystal polyester fiber of the present embodiment to a heat treatment, a liquid crystal polyester fiber having increased strength can be obtained.
[0087] [Strengthened liquid crystal polyester fiber and its manufacturing method] The method for producing the strengthened liquid crystal polyester fiber of the present embodiment includes a heat treatment step. In the heat treatment step according to the present embodiment, the liquid crystal polyester fiber wound on a bobbin or the like is heated in an oven or the like, whereby the liquid crystal polyester in the liquid crystal polyester fiber is made to have a high molecular weight, thereby improving the strength of the liquid crystal polyester fiber.
[0088] The heat treatment temperature in the heat treatment step according to this embodiment is 250°C or higher and 350°C or lower, preferably 270°C or higher and 340°C or lower, more preferably 280°C or higher and 330°C or lower, and even more preferably 290°C or higher and 320°C or lower.
[0089] When the heat treatment temperature is 250°C or higher, the liquid crystal polyester in the liquid crystal polyester fiber is likely to be increased in molecular weight. As a result, a liquid crystal polyester fiber with increased strength can be obtained. On the other hand, when the heat treatment temperature is 350°C or lower, there is little risk of the liquid crystal polyester in the liquid crystal polyester fiber melting. This prevents the liquid crystal polyester monofilaments from thermally fusing together, and the strength of the liquid crystal polyester monofilaments is likely to be exhibited. As a result, the strength of the entire liquid crystal polyester fiber is likely to be maintained.
[0090] The heat treatment time in the heat treatment step according to this embodiment is preferably from 0.5 hours to 50 hours, and more preferably from 1 hour to 20 hours.
[0091] The atmosphere during the heat treatment is preferably an inert gas atmosphere such as nitrogen or argon, or a vacuum with a degree of vacuum of 13.3 kPa (100 mmHg) or less. However, since liquid crystal polyesters tend to be easily hydrolyzed, it is preferable to use a dehumidified inert gas. For example, the dew point of the inert gas is preferably -20°C or less, more preferably -50°C or less.
[0092] As one aspect, in the heat treatment step according to the present embodiment, the liquid crystalline polyester fiber may be heat-treated by passing the liquid crystalline polyester fiber discharged from the nozzle portion 13 directly through a heating furnace. In another aspect, in the heat treatment step of the present embodiment, the liquid crystalline polyester fiber may be pulled out from a bobbin or the like after the winding step and then heat-treated.
[0093] The orientation degree of the liquid crystal polyester fiber in the length direction in the thus obtained high-strength liquid crystal polyester fiber is 90% or more and less than 100%, preferably 94% or more and less than 100%, and it has been found to be improved compared to the orientation degree of the liquid crystal polyester fiber in the length direction. This is believed to be because the orientation direction of the liquid crystal polyester fiber in the length direction is aligned as the molecular weight of the liquid crystal polyester in the liquid crystal polyester fiber increases.
[0094] The tensile strength of the strengthened liquid crystal polyester fiber of this embodiment is 25 cN / dtex or more and 30 cN / dtex or less. In another aspect, the tensile strength of the strengthened liquid crystal polyester fiber may be 26 cN / dtex or more and 30 cN / dtex or less, or 25 cN / dtex or more and 26 cN / dtex or less. The tensile strength of the strengthened liquid crystal polyester fiber of this embodiment is 3 times or more and 6 times or less than the tensile strength of the liquid crystal polyester fiber.
[0095] According to the present embodiment, a liquid crystalline polyester fiber having an increased tensile strength and a liquid crystalline polyester fiber having high strength can be obtained.
[0096] As one aspect, the liquid crystal polyester fiber of the present embodiment is a fiber containing a liquid crystal polyester, The liquid crystal polyester is The repeat unit (1) is a repeat unit derived from 6-hydroxy-2-naphthoic acid, the repeat unit (2) is a repeat unit derived from terephthalic acid and a repeat unit derived from 2,6-naphthalenedicarboxylic acid, and the repeat unit (3) is a repeat unit derived from hydroquinone, or The repeating unit (1) is a repeating unit derived from 6-hydroxy-2-naphthoic acid, the repeating unit (2) is a repeating unit derived from 2,6-naphthalenedicarboxylic acid, and the repeating unit (3) is a repeating unit derived from 4,4'-dihydroxybiphenyl, Relative to the total amount of all repeating units constituting the liquid crystal polyester, The content of the repeating unit (1) is 30 mol % or more, preferably 30 mol % or more and 80 mol % or less, more preferably 40 mol % or more and 70 mol % or less, and further preferably 45 mol % or more and 65 mol % or less, the content of the repeating unit (2) is 35 mol% or less, preferably from 10% to 35 mol%, more preferably from 15% to 30 mol%, and even more preferably from 17.5% to 27.5 mol%, the content of the repeating unit (3) is 35 mol% or less, preferably from 10% to 35 mol%, more preferably from 15% to 30 mol%, and even more preferably from 17.5% to 27.5 mol%, However, the total content of the repeating unit (1), the repeating unit (2) and the repeating unit (3) does not exceed 100 mol %; The liquid crystal polyester has a content of repeating units containing a 2,6-naphthylene group of 40 mol % or more and 85 mol % or less, preferably 65 mol % or more and 85 mol % or less, more preferably 65 mol % or more and 82 mol % or less, further preferably 68 mol % or more and 80 mol % or less, particularly preferably 70 mol % or more and 80 mol % or less, and extremely preferably 72 mol % or more and 77 mol % or less, based on the total content of all repeating units constituting the liquid crystal polyester; The orientation degree in the length direction of the liquid crystal polyester fibers is 89% or more and 95% or less, preferably 90% or more and 95% or less, more preferably 93% or more and 95% or less, and further preferably 94% or more and 95% or less; The tensile strength of the fiber is 5-8 cN / dtex. It is a liquid crystal polyester fiber.
[0097] As one aspect, the strengthened liquid crystal polyester fiber of the present embodiment has The orientation degree of the liquid crystal polyester in the length direction of the liquid crystal polyester fiber is 90% or more and less than 100%, preferably 94% or more and less than 100%; The tensile strength of the strengthened liquid crystal polyester fiber is 25 cN / dtex or more and 30 cN / dtex or less. It is a liquid crystal polyester fiber. EXAMPLES
[0098] Examples of the present invention will be described below, but the present invention is not limited thereto.
[0099] [Measurement of the degree of orientation of liquid crystal polyester fibers in the longitudinal direction] The orientation degree of the liquid crystal polyester fiber in the length direction was calculated based on the following formula (S1). The half-width W was determined by using a rotating anticathode type X-ray diffractometer RINT2500 manufactured by Rigaku Corporation, fixing the diffraction angle 2θ to a diffraction peak near 20°, and measuring the intensity distribution of the diffraction peak of the Debye ring from 0° to 360°. W in formula (S1) represents the half-width (unit: °) of the diffraction peak intensity. Fiber length orientation (%) = {(360-ΣW) / 360}×100 (S1)
[0100] [Measurement of tensile strength of liquid crystal polyester fiber] The tensile strength of the liquid crystal polyester fiber was measured at a measurement temperature of 23° C., a sample interval of 20 cm, and a pulling speed of 20 cm / min using an autograph AG-1KNIS manufactured by Shimadzu Corporation. The measurement was performed five times, and the average value was used.
[0101] [Measurement of Flow Initiation Temperature of Liquid Crystal Polyester] The flow initiation temperature of the liquid crystal polyester was measured using a flow characteristic evaluation device, "Flow Tester CFT-500" manufactured by Shimadzu Corporation. Approximately 2 g of sample was filled into a capillary rheometer equipped with a die with an inner diameter of 1 mm and a length of 10 mm, and the liquid crystal polyester was extruded from a nozzle at a heating rate of 4°C / min under a load of 9.8 MPa (100 kgf / cm2). The flow initiation temperature was determined as the temperature at which the melt viscosity was 4800 Pa·s (48,000 poise).
[0102] [Production Example 1] In a reactor equipped with a stirrer, torque meter, nitrogen gas inlet tube, thermometer and reflux condenser, 1034.99g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 272.52g (2.475 mol, 0.225 mol excess charge) of hydroquinone, 378.33g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.07g (0.5 mol) of terephthalic acid, 1226.87g (12.0 mol) of acetic anhydride and 0.17g of 1-methylimidazole as a catalyst were added, stirred at room temperature for 15 minutes, and then heated with stirring. When the internal temperature reached 145°C, stirring was continued for 1 hour while maintaining the temperature at 145°C.
[0103] The content of repeating units containing 2,6-naphthylene groups calculated from the amounts of raw material monomers charged was 72.5 mol %.
[0104] After that, 1.7 g of 1-methylimidazole was further added, and the temperature was raised to 310° C. over 3 hours and 30 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. After keeping at 310° C. for 3 hours, the liquid crystal polyester was taken out in a molten state into a tray to a thickness of 2 cm.
[0105] The liquid crystal polyester thus obtained was cooled to room temperature, solidified, and pulverized in a vertical pulverizer ("Orient VM-16" manufactured by Seishin Enterprise Co., Ltd.) to obtain a prepolymer powder having a particle size of about 0.1 mm to about 1 mm. A portion of the obtained prepolymer powder was taken out and its flow initiation temperature was measured, which was 266°C.
[0106] The prepolymer powder was heated from 25°C to 250°C over 1 hour, then heated from this temperature to 285°C over 7 hours, and further kept at 285°C for 5 hours to carry out solid-state polymerization. The powder after the solid-phase polymerization was cooled to obtain a powder of liquid crystal polyester (Resin A). The flow initiation temperature of the obtained liquid crystal polyester was measured and found to be 315°C.
[0107] [Production Example 2] In a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer and a reflux condenser, 987.90g (5.25 mol) of 2-hydroxy-6-naphthoic acid, 442.20g (2.375 mol) of 4,4'-dihydroxybiphenyl, 513.50g (2.375 mol) of 2,6-naphthalenedicarboxylic acid, 1229.80g (11.5 mol) of acetic anhydride and 0.17g of 1-methylimidazole as a catalyst were added, and the mixture was stirred at room temperature for 15 minutes, and then heated with stirring. When the internal temperature reached 145°C, the mixture was stirred for 1 hour while maintaining the temperature at 145°C.
[0108] The content of repeating units containing 2,6-naphthylene groups calculated from the amounts of raw material monomers charged was 76.3 mol %.
[0109] After that, 1.7 g of 1-methylimidazole was further added, and the temperature was raised to 310° C. over 3 hours and 30 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. After keeping at 310° C. for 3 hours, the liquid crystal polyester was taken out in a molten state into a tray to a thickness of 2 cm.
[0110] The liquid crystal polyester thus obtained was cooled to about room temperature, solidified, and pulverized in a vertical pulverizer ("Orient VM-16" manufactured by Seishin Enterprise Co., Ltd.) to obtain a prepolymer powder having a particle size of about 0.1 mm to about 1 mm. A portion of the obtained prepolymer powder was taken out and its flow initiation temperature was measured, which was 261°C.
[0111] The prepolymer powder was heated from 25°C to 250°C over 1 hour, then heated from this temperature to 285°C over 10 hours, and further kept at 285°C for 5 hours to carry out solid-state polymerization. The powder after solid-state polymerization was cooled to obtain a liquid crystal polyester powder (resin B). The flow initiation temperature of the obtained liquid crystal polyester was measured and found to be 324°C.
[0112] [Production Example 3] In a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 911g (6.6 mol) of p-hydroxybenzoic acid, 409g (2.2 mol) of 4,4'-dihydroxybiphenyl, 91g (0.55 mol) of isophthalic acid, 274g (1.65 mol) of terephthalic acid, and 1235g (12.1 mol) of acetic anhydride were added and stirred. Next, 0.17g of 1-methylimidazole was added to the mixture after stirring, and the inside of the reactor was sufficiently replaced with nitrogen gas, and then the temperature was raised to 150°C under a nitrogen gas flow over 15 minutes, and the temperature was maintained and refluxed for 1 hour.
[0113] The content of repeating units containing 2,6-naphthylene groups calculated from the amounts of raw material monomers charged was 0 mol %.
[0114] After that, 1.7 g of 1-methylimidazole was further added, and the temperature was raised to 320° C. over 2 hours and 50 minutes while distilling off the by-product acetic acid and unreacted acetic anhydride. The reaction was deemed to have ended when an increase in torque was observed, and the contents were removed.
[0115] A prepolymer powder having a particle size of about 0.1 mm to about 1 mm was obtained in the same manner as in Production Example 1. A portion of the obtained prepolymer powder was taken out and its flow initiation temperature was measured, which was 257°C.
[0116] The prepolymer powder was heated from 25°C to 250°C over 1 hour, then heated from this temperature to 270°C over 2.5 hours, and further kept at the same temperature for 5 hours to carry out solid-state polymerization. The powder after solid-state polymerization was cooled to obtain a liquid crystal polyester powder (resin C). The flow initiation temperature of the obtained liquid crystal polyester was measured and found to be 316°C.
[0117] [Production Example 4] A reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser was charged with 1209.9 g (8.76 mol) of 4-hydroxybenzoic acid, 609.7 g (3.24 mol) of 6-hydroxy-2-naphthoic acid, and 1347.6 g (13.2 mol) of acetic anhydride. The atmosphere inside the reactor was thoroughly replaced with nitrogen gas, and the temperature was raised to 150° C. under a nitrogen gas stream over 15 minutes, and the temperature was maintained while refluxing for 3 hours.
[0118] The content of repeating units containing 2,6-naphthylene groups calculated from the amounts of raw material monomers charged was 27.0 mol %.
[0119] Thereafter, the temperature was raised to 290° C. over 4 hours while distilling off the by-product acetic acid and unreacted acetic anhydride. After keeping at 290° C. for 1.5 hours, the liquid crystal polyester was taken out in a molten state into a tray to a thickness of 2 cm.
[0120] A prepolymer powder having a particle size of about 0.1 mm to about 1 mm was obtained in the same manner as in Production Example 1. A portion of the obtained prepolymer powder was taken out and its flow initiation temperature was measured, which was 235°C.
[0121] The prepolymer powder was heated from 25°C to 265°C over 10 hours, then heated from this temperature to 265°C over 7 hours, and further kept at the same temperature for 5 hours to carry out solid-state polymerization. The powder after the solid-phase polymerization was cooled to obtain a liquid crystal polyester powder (Resin D). The flow initiation temperature of the obtained liquid crystal polyester was measured and found to be 288°C.
[0122] [Examples 1 to 3, Comparative Examples 1 to 10] The liquid crystal polyesters obtained in Production Examples 1 to 4 were melt-kneaded at the processing temperatures shown in Table 1 using a twin-screw extruder (PCM-30) manufactured by Ikegai Iron Works Co., Ltd., and granulated into pellets.
[0123] Next, using a multifilament spinning device "Polymer Mate V" manufactured by Chubu Chemical Machinery Co., Ltd., the molten liquid crystal polyester was filtered through a filter (made of stainless steel), and then discharged from a nozzle with a hole diameter of 0.15 mm and 24 holes under the conditions of Table 1, and the fiber obtained by melt spinning was wound on a metal bobbin with holes. The orientation degree and tensile strength of the liquid crystal polyester fiber in the length direction of the liquid crystal polyester fiber were measured, and the measurement results are shown in Table 2.
[0124] The liquid crystal polyester fiber was wound around a bobbin and then heat-treated under the conditions shown in Table 1. The orientation degree in the length direction of the liquid crystal polyester fiber and the tensile strength of the liquid crystal polyester fiber thus obtained after the heat treatment were measured. The measurement results are shown in Table 2.
[0125] [Table 1]
[0126] [Table 2]
[0127] From the results shown in Tables 1 and 2, it was found that the liquid crystalline polyester fiber to which one embodiment of the present invention is applied has an improved tensile strength.
[0128] From the above, it has been demonstrated that the present invention is useful. [Industrial Applicability]
[0129] INDUSTRIAL APPLICABILITY According to the present invention, it is possible to provide a liquid crystal polyester fiber from which a liquid crystal polyester fiber having increased strength and a liquid crystal polyester fiber having high strength can be obtained, and therefore the present invention is extremely useful industrially. [Explanation of symbols]
[0130] 1. Spinning equipment 11 Extruder 12 Gear pump 13 Nozzle section 14 Take-off roller 15 Winding section 16 Resin flow path
Claims
1. A fiber comprising a liquid crystalline polyester, The liquid crystal polyester has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3), at least one repeating unit selected from the group consisting of a repeating unit represented by formula (1), a repeating unit represented by formula (2), and a repeating unit represented by formula (3) contains a 2,6-naphthylene group; the content of the repeating unit containing the 2,6-naphthylene group is 40 mol % or more based on the total content of all repeating units constituting the liquid crystal polyester, The orientation degree of the fibers in the length direction of the liquid crystal polyester is 89% or more and 95% or less, The fiber diameter is 5 to 100 μm. Liquid crystal polyester fiber. (1) -O-Ar1-CO- (2) -CO-Ar2-CO- (3) -X-Ar3-Y- (Ar1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar2 and Ar3 each independently represent a phenylene group, a naphthylene group, or a biphenylylene group; and at least one selected from the group consisting of Ar1, Ar2, and Ar3 includes a 2,6-naphthylene group. X and Y each independently represent an oxygen atom or an imino group (-NH-). Hydrogen atoms in the group represented by Ar1, Ar2, or Ar3 may each independently be substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.)
2. 2. The liquid crystal polyester fiber according to claim 1, wherein the content of the repeating unit containing the 2,6-naphthylene group is 65 mol % or more and 85 mol % or less based on the total content of all repeating units constituting the liquid crystal polyester.
3. A fiber comprising a liquid crystalline polyester, The tensile strength is 25 cN / dtex or more and 30 cN / dtex or less, The orientation degree of the liquid crystal polyester fibers in the length direction is 94% or more and less than 100%, The liquid crystal polyester has a repeating unit represented by the following formula (1), a repeating unit represented by the following formula (2), and a repeating unit represented by the following formula (3), at least one repeating unit selected from the group consisting of a repeating unit represented by formula (1), a repeating unit represented by formula (2), and a repeating unit represented by formula (3) contains a 2,6-naphthylene group; the content of the repeating unit containing the 2,6-naphthylene group is 40 mol % or more based on the total content of all repeating units constituting the liquid crystal polyester, The fiber diameter is 5 to 100 μm. Liquid crystal polyester fiber. (1) -O-Ar1-CO- (2) -CO-Ar2-CO- (3) -X-Ar3-Y- (Ar1 represents a phenylene group, a naphthylene group, or a biphenylylene group; Ar2 and Ar3 each independently represent a phenylene group, a naphthylene group, or a biphenylylene group; and at least one selected from the group consisting of Ar1, Ar2, and Ar3 includes a 2,6-naphthylene group. X and Y each independently represent an oxygen atom or an imino group (-NH-). Hydrogen atoms in the group represented by Ar1, Ar2, or Ar3 may each independently be substituted with a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.)
4. 4. The liquid crystal polyester fiber according to claim 3, wherein the content of the repeating unit containing the 2,6-naphthylene group is 65 mol % or more and 85 mol % or less based on the total content of all repeating units constituting the liquid crystal polyester.
Citation Information
Patent Citations
Aromatic polyester fiber having high strength and high modulus of elasticity
JP1991294517A
Material for producing fiber, fiber using the material, and nonwoven fabric
JP2010043380A
Rubber reinforcing material, tire cord, and tire
JP2012031556A
Liquid crystalline polyester multifilament
JP2017166110A
Tire bead fiber
WO2017022589A1